2002
DOI: 10.1074/jbc.m206149200
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Molecular Mechanisms Involved in the Transcriptional Activation of the CHOP and Asparagine Synthetase Genes in Response to Amino Acid Deprivation or Activation of the Unfolded Protein Response

Abstract: A promoter element called the amino acid response element (AARE), which is essential for the induction of CHOP (a CCAAT/enhancer-binding protein-related gene) transcription by amino acid depletion, has been previously characterized. Conversely, the human asparagine synthetase (AS) promoter contains two cis-acting elements termed nutrient-sensing response elements (NSRE-1 and NSRE-2) that are required to activate the gene by either amino acid deprivation or the endoplasmic reticulum stress response. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
65
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 39 publications
3
65
0
Order By: Relevance
“…response elements nor nutrient-sensing response elements could be identified on the ASS proximal promoter (17) in contrast to CHOP (C/EBP homology protein) and asparagine synthase genes (27,28). Additionally, a number of transcription factors, namely activator protein-1 (AP-1 (29)), hepatocyte nuclear factor-1 (HNF-1 (30)), activating transcription factor-4 (ATF-4) (28) and -2 (31), and C/EBP␤ (32), were also involved in the regulation of the expression of genes by amino acids, but again the responsive elements to these transcription factors were not identified on the ASS gene promoter.…”
Section: Discussionmentioning
confidence: 99%
“…response elements nor nutrient-sensing response elements could be identified on the ASS proximal promoter (17) in contrast to CHOP (C/EBP homology protein) and asparagine synthase genes (27,28). Additionally, a number of transcription factors, namely activator protein-1 (AP-1 (29)), hepatocyte nuclear factor-1 (HNF-1 (30)), activating transcription factor-4 (ATF-4) (28) and -2 (31), and C/EBP␤ (32), were also involved in the regulation of the expression of genes by amino acids, but again the responsive elements to these transcription factors were not identified on the ASS gene promoter.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore propose that the cat-1 promoter contains a separate ER response element. The CHOP gene also has different promoter elements that regulate transcription during amino acid starvation and ER stress (16,17). Induction of CHOP transcription by ER stress requires an ATF composite site, which is involved in amino acid control, and a second element that is unique to ER stress (17).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, amino acid starvation stimulates the transcription of many genes by a well characterized mechanism involving the regulator GCN4 (14). The situation is less well studied in mammalian cells, with only two genes, asparagine synthetase (AS) and C/EBP homologous protein (CHOP), studied in detail at the molecular level (15)(16)(17). The transcription of these genes is stimulated by both amino acid starvation and the UPR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This modulation may involve the activation of specific intracellular pathways involved in protein synthesis, including activation of the mammalian target of rapamycin (mTOR) pathway. It has been observed that mTor responds immediately to any modification in aminoacid or energy consumption (Bruhat et al, 2002;Asnaghi et al, 2004). When aminoacid storage, particularly leucine, is elevated, mTOR interacts with other proteins to form protein complexes in order to phosphorylate their key-components, which are in turn responsible for translating mRNA into proteins.…”
mentioning
confidence: 99%